Role of Zn2+ Substitution on the Magnetic, Hyperthermic, and Relaxometric Properties of Cobalt Ferrite Nanoparticles - Albino, Martin; Fantechi, Elvira; Innocenti, Claudia; López-Ortega, Alberto; Bonanni, Valentina; Campo, Giulio; Pineider, Francesco; Gurioli, Massimo; Arosio, Paolo; Orlando, Tomas; Bertoni, Giovanni; de Julián Fernández, Cesar; et al. (Journal of physical chemistry. C, 2019)
Zinc substitution is often proposed as an efficient strategy to improve the performances of spinel ferrite nanoparticles, particularly related to their application as theranostic agents. In this work, a series of 8 nm spinel ferrite nanoparticles of formula Co x Zn y Fe3–(x+y)O4 is synthesized by thermal decomposition with the purpose of investigating the role of Zn2+ ions in modifying the structural and magnetic properties. Contrary to most of the literature on this subject, where the sum of Co and Zn is kept constant (x + y = 1), here, the amount of Co is maintained at ca. x = 0.6, corresponding to the maximum of magnetic anisotropy of the Zn-undoped system, whereas the amount of Zn is progressively varied along the series from y = 0.05 to 0.4. This approach allows enlightening the effect of the Zn introduction on the magnetic and crystal structures and, particularly, on magnetic anisotropy, which is deeply investigated by several complementary techniques. A significant increase of the saturation magnetization, M S, upon the Zn content up to y = 0.4 is confirmed only at low temperature, whereas at room temperature, this effect is partially nullified by the weakening of the magnetic exchange coupling constants due to the increasing Zn substitution. Moreover, we demonstrate that the lattice modifications following the Zn introduction are responsible of a strong decrease of the particle magnetic anisotropy. Overall, these effects limit the use of Zn-substituted ferrites in biomedical applications like magnetic resonance imaging and magnetic fluid hyperthermia only to very low amount of Zn, as here confirmed by relaxometric and calorimetric measurements.